2019
DOI: 10.1055/s-0039-1693464
|View full text |Cite|
|
Sign up to set email alerts
|

Use of Prophylaxis for Prevention of Venous Thromboembolism in Patients with Isolated Foot or Ankle Surgery: A Systematic Review and Meta-Analysis

Abstract: Although prophylaxis for venous thromboembolism (VTE) is recommended after many surgeries, evidence base for use of VTE prophylaxis after foot or ankle surgery has been elusive, leading into varying guidelines recommendations and notable practice variations. We conducted a systematic review of the literature to determine if use of VTE prophylaxis decreased the frequency of subsequent VTE, including deep vein thrombosis (DVT) or pulmonary embolism (PE), compared with control. We searched PubMed, the Cochrane Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Surgeons seeking recommendations for VTE chemoprophylaxis following traumatic injury distal to the knee continue to find limited guidance despite numerous systematic reviews and meta-analyses on the topic. [17][18][19] Secondary studies repeatedly mention quality of evidence as the main factor hindering consensus, and many provide a brief assessment of methodological quality or risk of bias. [18][19][20][21] However, this study investigated the strength of evidence via qualitative assessment of the primary literature.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons seeking recommendations for VTE chemoprophylaxis following traumatic injury distal to the knee continue to find limited guidance despite numerous systematic reviews and meta-analyses on the topic. [17][18][19] Secondary studies repeatedly mention quality of evidence as the main factor hindering consensus, and many provide a brief assessment of methodological quality or risk of bias. [18][19][20][21] However, this study investigated the strength of evidence via qualitative assessment of the primary literature.…”
Section: Discussionmentioning
confidence: 99%
“…This must be kept firmly in mind when interpreting studies. For example, a recent meta-analysis that incorporated six prospective randomized controlled trials (RCT) comprising 1,600 patients undergoing isolated F&A surgery found a rate of VTE of 8.3% among patients with chemoprophylaxis as compared to 11.7% without (relative risk [RR] 0.72, 95% confidence interval [CI] 0.55 - 0.94, p = 0.02) 56 . It concluded that, while chemoprophylaxis is efficacious, “event rates are low and symptomatic events are rare”.…”
Section: - Concerning Vte Risk Which Surgeries Can Be Considered Majo...mentioning
confidence: 99%
“…Although pharmacomechanical interventions combined with thrombolytic therapy, can rapidly remove thrombus and improve outcomes in patients with acute deep vein thrombosis, these benefits could not be observed among the sub-group for whom this was even associated with increased bleeding. The findings exposed in the systematic review and meta-analysis from Bikdeli et al 18 also invite us to rethink mainstay venous thromboembolism (VTE) prophylaxis recommendation in the particular context of foot-ankle surgery. Using a well-recognised national administrative database, Jung et al 19 challenged strict adherence to the reference stroke risk CHA 2 DS 2 -VASc score for atrial fibrillation (AF) patients with hypertrophic cardiomyopathy.…”
Section: Defining Narrower Target Groups To Fine-tune Clinical Managementioning
confidence: 99%